2017
DOI: 10.3389/fimmu.2017.01509
|View full text |Cite
|
Sign up to set email alerts
|

Will a mAb-Based Immunotherapy Directed against Cancer Stem Cells Be Feasible?

Abstract: The cancer stem cell (CSC) hypothesis suggests that within a tumor, there is a small subpopulation of cells with stem cell properties responsible for tumor maintenance and metastasis generation. This hypothesis also implies that new antitumor drugs, rather than targeting the bulk of the tumor mass, would be more effective if they directly targeted the CSC subpopulation. The CSCs from several types of tumors have been identified with mAbs recognizing surface antigens in these cells; however, antigens specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…For example, monoclonal antibodies against NOTCH have been shown to reduce the cancer stem cell (CSC) population in CRC tumors [ 37 ], with clinical trials of therapeutic antibodies against DLL4 in combination with FOLFIRI (irinotecan, folic acid, leucovorin, and fluorouracil), ongoing in the metastatic CRC setting ( NCT01189942 ). Another clinical trial employs the anti-DLL4 antibody demcizumab, in combination with the anti-PD-1 antibody pembrolizumab (immune checkpoint inhibitor) in metastatic solid tumors ( NCT02722954 ) [ 38 ]. Understanding pathophysiologic mechanisms of potential hepato-toxicities in these settings thus continues to hold significant clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, monoclonal antibodies against NOTCH have been shown to reduce the cancer stem cell (CSC) population in CRC tumors [ 37 ], with clinical trials of therapeutic antibodies against DLL4 in combination with FOLFIRI (irinotecan, folic acid, leucovorin, and fluorouracil), ongoing in the metastatic CRC setting ( NCT01189942 ). Another clinical trial employs the anti-DLL4 antibody demcizumab, in combination with the anti-PD-1 antibody pembrolizumab (immune checkpoint inhibitor) in metastatic solid tumors ( NCT02722954 ) [ 38 ]. Understanding pathophysiologic mechanisms of potential hepato-toxicities in these settings thus continues to hold significant clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…e past two decades have brought into limelight the significance and feasibility of monoclonal antibodies-(mAb-) based treatments as therapies against cancer treatment. Antibody-drug conjugates are powerful newer discovered weapons for the fight against cancer [130], and immunomodulatory antibodies, illustrated by anti-PD-L1, anti-PD-1, and immune checkpoints targeting anti-CTLA-4 antibodies, have also recently attained outstanding clinical success (discussed in immune checkpoints). e expression levels of some markers (Table 1) in CSCs considerably dissimilar to the other tumor cells, which provides promising targets for antibody-based immunotherapy.…”
Section: Antibody-based Immunotherapymentioning
confidence: 99%
“…Outstandingly, HER2 expression can also be targeted in GBM CSCs [143]. As the "CSC markers" may not necessarily be unique to CSCs, single-agent mAb therapy may adversely affect normal cells [130]. Combination therapy using an assortment of different antibodies targeting multiple CSC markers could potentially reduce doses of individual antibodies to accomplish the efficient abolishment of CSCs while reducing side effects due to huge concentrations of single anti-CSC mAbs.…”
Section: Antibody-based Immunotherapymentioning
confidence: 99%
“…It has recently been demonstrated that CSCs play critical roles in resistance to anticancer treatment and are responsible for metastasis in several human malignancies, including PDAC[12]. CSCs are rare immortal tumour cells, which have the ability to self-renew, produce differentiated progeny, form tumours in mice, and form non-adherent spheroids called tumour-spheres in vitro [13,14]. CSCs are more resistant than non-CSCs to chemotherapy and radiotherapy treatments because they have higher expression levels of anti-apoptotic proteins, ABC transporters, and multidrug resistance genes[15].…”
Section: Pcscsmentioning
confidence: 99%